Current situation of the medical student in Colombia - Gómez-Bastidas, Luna V. (2021)
The essence of Medicine is service to the human being, and its teaching is carried out through the clinical method and a set of skills that the student must acquire throughout his training. However, it is possible that there is a pedagogical problem in the current model that makes doctors and students feel dissatisfied with their academic process, affecting their professional lives. The purpose of this review is to present some aspects that are experienced as a medical student in Colombia, the implications that the use of technology has had in medical training, and its impact on work and academic life.